Kelayakan Finansial PLTP Atadei Berbasis Risiko Investasi - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Maria Anjelina Peni (JTM : JURNAL TEKNIK MESIN, 2026)
This study evaluates the financial feasibility and risk profile of the planned Atadei Geothermal Power Plant in Lembata, East Nusa Tenggara, with an installed capacity of 2 x 5 MW. The analysis applies a quantitative pre-feasibility approach using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), Benefit Cost Ratio (BCR), and Profitability Index (PI). Two operating assumptions are compared: a constant case with a 90% capacity factor and constant OPEX, and a realistic case with capacity factor declining from 90% to 75% and OPEX escalating by 2.3% per year. The constant assumption shows that the project is feasible in the moderate scenario with NPV of USD 1,942,068 and in the optimistic scenario with NPV of USD 11,369,779, while the pessimistic scenario remains infeasible. Under realistic assumptions, feasibility decreases sharply; only the optimistic scenario remains marginally feasible with NPV of USD 81,098, BCR of 1.00, PI of 1.00, and a payback period of 30.45 years. These findings indicate that discount rate, OPEX escalation, and reservoir-related production decline are the dominant risks. The project can support regional energy security, but it requires low-cost financing, stable reservoir performance, and strict operational cost control